THE ROLE OF GOVERNMENT IN THE ECONOMY - Muhammad Akram Khan (International Institute of Islamic Thought, 1997)
Introduction The recent past has seen fundamental changes in the government’s role in the economy. With the defeat of socialism and the worldwide onslaught of privatization, a new scenario is emerging. The direct role of government is shrinking and its indirect role is increasing. Arguably, privatization does not necessarily mean “no government,” but rather “better government.” As a result, the following new issues are emerging: What is the extent and nature of government regulation in the economy? How can government play an effective role in the redistribution of economic power and still keep the free market economy undisturbed? What structural changes are necessary to protect the public interest? How can government itself be regulated? How can we prevent government from becoming an instrument of injustice and tyranny? The present paper seeks to discuss these questions from the Islamic perspective. Need for Government We need government to provide the fundamental legal and social framework for a free market economy. This framework implies necessary laws that define the property and other rights, enforce contracts, and describe the status and form of various business organizations. We need government to define the rules of the game. Through legislation the government acts as a referee and forbids foul play. It prohibits cheating and the sale of adulterated foods and drugs; it establishes ...